Liposuction-Assisted Short-Scar Brachioplasty: Technical Highlights. Issue 3 (September 2016) - Hill, Sean; Small, Kevin H.; Pezeshk, Ronnie A.; Rohrich, Rod J.
Abstract : Summary: Upper arm contouring is based on the location and amount of excess skin and fat. The short-scar brachioplasty addresses minimal to moderate skin laxity and lipodystrophy in the proximal arm in patients with appropriate skin tone and quality. This article highlights technical refinements of the senior author's (R.J.R.) approach to short-scar medial liposuction-assisted brachioplasty to maximize results and minimize incision length. To highlight this simple and safe approach with high patient/surgeon satisfaction, the authors discuss the following in this Video Plus article: patient examination, preoperative assessment, surgical pearls, and postoperative outcomes. Abstract : Supplemental Digital Content is Available in the Text.